Reliabilitas Lembaga Jaminan Fidusia dalam Sistem Hukum Jaminan Indonesia - Alfis Setyawan; Agustianto Agustianto; Windi Afdal (Journal of Judicial Review, 2018)
This study aims to: 1) review the reliability of the institution, fiduciary can access the creditor to pay the settlement of obligations from the debtor; 2) to find out the form of law (legal adjusment) that can be done in practices that cannot be overcome or have been minimized the contractor. The research was conducted using empirical legal research methods. In this empirical legal study, research is carried out by collecting primary data as secondary data supporting material. Primary data is obtained through structured and in-depth interviews with informants. Secondary data is obtained by reviewing the literature (library research) from primary, secondary and tertiary legal materials. Based on field studies and literature, primary data and secondary data are then processed and analyzed descriptively-analytically. Described descriptive data analysis techniques to provide an explanation of how to apply fiduciary institutions in Batam City. Meanwhile this research is also analytical because in the end it will question again how the relationship between legal principles that exist in the law can work in its social container. This study is expected to provide an explanation of the reliability of fiduciary institutions in Batam City. Reliability will be adjusted to the provisions that can be used with the fiduciary guarantee binding certificate and the quality of the fiduciary IS itself by using objects that can be used as creditors as an instrument for repayment of obligations. It is worth offering to find gaps hidden in the room that the creditor will do several things in preparing the binding of fiduciary guarantees. Based on this knowledge can be used and recommended with the legal policy in Indonesia.